PENGEMBANGAN ASESMEN PEMECAHAN MASALAH UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH, PENGUASAAN KONSEP, DAN PERUBAHAN KONSEPSI MAHASISWA BERDASARKAN DIMENSI GAYA KOGNITIF DAN KEMAMPUAN BERPIKIR LOGIS PADA TOPIK KELISTRIKAN DAN KEMAGNETAN - Rahmawati, - (2020)
The R and D study about developing performance assessment for problem solving skills which involve a number of students (n=30) in Electricity and Magnetism course in one university in Makasar was conducted to improve problem solving skills, concept mastery, and conceptual change based on cognitive style and logical thinking in electricity topics. R&D design consists of three stages, namely the preliminary study, planning, and development stages. A number of instruments used in this study were in the form of problem-solving group worksheets and practical activities, observation sheets, assessment rubrics, questionnaires, and tests (problem solving skills, four-tier test conception diagnostics, concept mastery, TOLT, and GEFT). Data were analyzed statistically descriptive, N-Gain, and non-parametric inferential (Kruskal-Wallis and Mann Whitney). The characteristics of problem solving assessment developed are problem-based performance assessment which consists of process and product performance. The results showed that there were differences between the Field Independence (FI) and Field Dependence (FD) groups in improving problem solving skills, concept mastery, and changing the conception level in FI students, there were no misconceptions on the initial and final tests. The percentage of FD students at the level of misconception at the initial test was higher than on the last test. There are significant differences between the FI and FD groups in problem solving skills and concept mastery. Increased N-Gain values between concrete and transitional are moderate while in formal group in high in KPM; N-Gain values in TPK were minimum limit of moderate for concrete and maximum limit moderate for transitional, and high for formal group. There were significant differences among the three groups on problem solving skill and concept mastery. In the formal group there were no misconceptions for both the initial and final tests. Therefore, students with concrete and transitional operation had misconception at the initial and the last test. For psychomotor aspects, FI students are better than FD students. In terms of the level of logical thinking ability, students with formal operations are better at conducting practical activities than transitional and concrete students.